Trade Union Responses to Transnational Labour Mobility in the Finnish-Estonian Context - Alho, Rolle (Nordic Journal of Working Life Studies, 2013)
This article examines trade union strategies in relation to labor migration in Estonia and Finland, drawing on face-to-face interviews with trade unionists and official union statements. The study considers the national trade union strategies located in two separate but interconnected localities that represent different approaches to market economy. Previous research suggests that the national industrial relations system is a key factor in explaining unions’ labor migration strategies. Unions operating in liberal market economies are claimed to be more open toward immigration and more inclusive toward immigrants than unions in coordinated markets. This study analyzes the extent to which this theory holds in the context of Estonia and Finland—Finland representing a coordinated market economy and Estonia a liberal market economy. Furthermore, the analysis examines how the emergence of a translocal labor market, resulting from the geographical vicinity and linguistic affinity between Finland and Estonia as well as from free mobility within the EU, is reflected in trade union approaches to labor migration. The study finds that Finnish trade union strategies influence labor mobility, whereas Estonian trade unions remain bystanders in the issue.